The effect of β-glucan prebiotic fibre (oats) on the gut microbiome of chronic kidney disease patients (Stage IV and V) and impact on kidney function - Ebrahim, Zarina (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.